1993
DOI: 10.2172/10183335
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the effects of thread placement on the Kendall Square KSR1

Abstract: This paper describes a meuurement study of the effects of thread placement on memory access times on the Kendall Squ_re multiprocessor, the KSRI. The KSRI uses a conventions] shared memory prograunming mode] in a d_stributed memory axchitecture. The &rchitecture is b_ed on a ring of rings of 64-bit superscalar microprocessors. The KSRI has a Cache-Only Memory Architecture (COMA). Memory consists of the local cache memories attached to each processor. Whenever an address is accessed, the data item is automatica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
1997
1997

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…We have observed that reads leading to coherence misses on write-invalidate architectures (interprocess reads) occur in bursts in simple programs like sort and complex application programs like the Splash benchmarks [12]. We also have verified the suggestion of [15] and [9] that programs with identical average read sharing characteristics can vary significantly in execution time due to differences in sharing at small time scales. This work involved a cache-only memory architecture that included a form of cache update called read-broadcast.…”
Section: Introductionmentioning
confidence: 66%
“…We have observed that reads leading to coherence misses on write-invalidate architectures (interprocess reads) occur in bursts in simple programs like sort and complex application programs like the Splash benchmarks [12]. We also have verified the suggestion of [15] and [9] that programs with identical average read sharing characteristics can vary significantly in execution time due to differences in sharing at small time scales. This work involved a cache-only memory architecture that included a form of cache update called read-broadcast.…”
Section: Introductionmentioning
confidence: 66%
“…Wagner et al [7] studied the impact of thread placement on performance using a set of synthetic benchmarks. They conducted experiments on a two-ring 64-processor system.…”
Section: Relevant Workmentioning
confidence: 99%